2014
DOI: 10.3389/fbioe.2014.00009
|View full text |Cite
|
Sign up to set email alerts
|

Vibrating Makes for Better Seeing: From the Fly’s Micro-Eye Movements to Hyperacute Visual Sensors

Abstract: Active vision means that visual perception not only depends closely on the subject’s own movements, but that these movements actually contribute to the visual perceptual processes. Vertebrates’ and invertebrates’ eye movements are probably part of an active visual process, but their exact role still remains to be determined. In this paper, studies on the retinal micro-movements occurring in the compound eye of the fly are reviewed. Several authors have located and identified the muscles involved in these small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Here, we present a new visual sensor and its innovative pan-tilt system which weight less than 50 g once assembled. This new eye is composed of: 1) a gimbal system, reproducing the decoupling between the head (center of vision) and the body existing on most animals, 2) a visual sensor inspired from the vision of the fly (for a review see [18]) and 3) a vibration mechanism which endows the visual sensor of hyperacuity, making it possible to locate accurately a target with only few pixels. The choice of using a gimbal system was motivated by the fact that it allows to separate the flight stability task (rejection of disturbances, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present a new visual sensor and its innovative pan-tilt system which weight less than 50 g once assembled. This new eye is composed of: 1) a gimbal system, reproducing the decoupling between the head (center of vision) and the body existing on most animals, 2) a visual sensor inspired from the vision of the fly (for a review see [18]) and 3) a vibration mechanism which endows the visual sensor of hyperacuity, making it possible to locate accurately a target with only few pixels. The choice of using a gimbal system was motivated by the fact that it allows to separate the flight stability task (rejection of disturbances, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…We discover that by actively modulating light input and photoreceptor output, these processes reduce motion blur during saccades and adaptation during gaze fixation, which otherwise could fade vision (Ditchburn & Ginsborg, 1952;Riggs & Ratliff, 1952;Land, 1997). The resulting phasic responses sharpen retinal images by highlighting the times when visual objects cross a photoreceptor's receptive field, thereby encoding space in time (see also : Ahissar & Arieli, 2001;Donner & Hemilä, 2007;Rucci et al, 2007;Kuang et al, 2012a;Kuang et al, 2012b;Franceschini et al, 2014;Viollet, 2014). Thus, neither saccades nor fixations blind the flies, but together improve vision.Incorporation of this novel opto-mechano-electric mechanism into our 'microsaccadic sampling'-model predicts that Drosophila can see >4-fold finer details than their eyes' spatial sampling limita prediction directly confirmed by optomotor behavior experiments.…”
mentioning
confidence: 98%
“…This would be true without the existence of the fly's active visual processing system based on retinal micro vibrations. Since the 1970s, several studies have shown that active retinal micro movements occur in flies, but the exact function of these micro movements and how they contribute to improving the visual acuity have not yet been established [57]. However, several authors have integrated micro movements of this kind into their artificial visual sensors, and the results obtained have shown that they were able to locate a contrasting target with much greater accuracy (up to 700-fold) than that achieved using optical systems alone [22,57].…”
Section: Fly-inspired Hyperacute Sensormentioning
confidence: 99%
“…Since the 1970s, several studies have shown that active retinal micro movements occur in flies, but the exact function of these micro movements and how they contribute to improving the visual acuity have not yet been established [57]. However, several authors have integrated micro movements of this kind into their artificial visual sensors, and the results obtained have shown that they were able to locate a contrasting target with much greater accuracy (up to 700-fold) than that achieved using optical systems alone [22,57]. Thanks to this hyperacuity, it was recently established using a biorobotic approach that a contrasting moving target (moving hands) could be located on a textured background and the distance travelled by a micro robot flying above a textured plane could be measured by processing the visual signals conveyed by the 40 ommatidia in a vibrating artificial compound eye [8].…”
Section: Fly-inspired Hyperacute Sensormentioning
confidence: 99%